Correlations among the Number of Somatic Cells and Lactose Content in Bovine Milk - Adina-Mirela Ariton; Andra-Sabina Neculai-Văleanu; Ioana Porosnicu; Ciprian Radu; Lucia-Carmen Trincă (Scientific Papers Animal Science and Biotechnologies, 2023)
Bovine mastitis, defined as the inflammation of the mammary gland, is the most important diseases of the mammary gland in cows due to the considerable losses in milk production and the danger that milk from ill cows poses to public health. The number of somatic cells in milk is the most important indicator used for directly evaluating the condition of the mammary gland and the quality of the milk. The development of inflammatory disease in the mammary gland is indicated by somatic cell counts above 200 000 cells per millilitre. Differences in the composition of milk, such as its lactose content, are related to variations in the number of somatic cells. The present paper summarizes the current knowledge regarding the correlations between lactose content and milk somatic cell count, and the potential of this parameters as a biomarker for assessing udder health status in modern dairy cow health prevention programs.